2019
DOI: 10.1002/ps.5457
|View full text |Cite
|
Sign up to set email alerts
|

Topical dsRNA delivery induces gene silencing and mortality in the pea aphid

Abstract: BACKGROUND: With the growing number of available aphid genomes and transcriptomes, an efficient and easy-to-adapt tool for gene function study is urgently required. RNA interference (RNAi), as a post-transcriptional gene silencing mechanism, is important as a research tool for determining gene functions and has potential as a novel insect control strategy. However, these applications have been hampered by the lack of effective dsRNA delivery approaches in aphids. RESULTS:Here, we developed a convenient and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…Therefore, we tried two different RNAi methods to deliver siRNA into the cotton mealybugs. RNAi delivery methods have been documented in various insects, including hemipteran species [29,37,[49][50][51][52]. The microinjection method is the most common method for RNAi delivery in scientific research and is time-consuming and requires a high degree of technical skill.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we tried two different RNAi methods to deliver siRNA into the cotton mealybugs. RNAi delivery methods have been documented in various insects, including hemipteran species [29,37,[49][50][51][52]. The microinjection method is the most common method for RNAi delivery in scientific research and is time-consuming and requires a high degree of technical skill.…”
Section: Discussionmentioning
confidence: 99%
“…In each treatment, 30 adult gravid females were pooled into a single biological replicate and injected with 0.5 µg siRNA each. Approximately 30 pupae in each biological replicate were treated using the topical RNAi-based siRNA delivery method in which a few drops were applied to the dorsal side of the pupa abdomen at a final concentration of~500 ng/µL following the methods described by [37]. The control groups underwent the same procedures under the same conditions, and all experiments were performed in triplicate.…”
Section: Rna Inferencementioning
confidence: 99%
“…Although, topical exposure of the pea aphid nymphs to biopesticides (i.e. target gene-specific dsRNA) was reported to be effective, 24 no previous study has reported topical exposure of aphids to peptide analogues. In this study, after treatment with CAPA-PK analogues, two effects were observed, namely a rapid effect (within 5 days) on survival was recorded for 17%-47% of the aphids while a long-lived effect on fecundity was observed in surviving aphids.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi (normally inferred to as the siRNA pathway) is a promising tool for aphid control [32][33][34] but RNAi use in effective pest control remains a challenge. This is due to gene silencing efficacies (both RNA and protein level), pest control efficacy (mortality), field delivery systems and potential resistance development [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, these genes are rarely investigated using experimental approach. There is a need to study three pathways of RNAi activity as a possible aphid control strategy [32][33][34]. To explore the potential role of these expanded genes in three sub-pathways of RNAi, the expressions of 25 core RNAi genes were detected in different development stages, various tissues, dsRNA-treated samples, and miRNA-treated samples.…”
Section: Introductionmentioning
confidence: 99%